Zooplankton biodiversity in the biosphere reserve of Cu Lao Cham - Hoi An, 2015–2016 - Truong, Trinh Si Hai; Nguyen, Vinh Tam (Vietnam Journal of Marine Science and Technology, 2019)
Zooplankton samples in the biosphere reserve of Cu Lao Cham - Hoi An were collected at 20 stations belonging to 3 ecosystems: Mangrove palm - seagrass, transition area and coral reef in rainy season (11/2015) and dry season (6/2016) to determine biodiversity of the biosphere reserve of Cu Lao Cham - Hoi An.  161 species belonging to 16 zooplankton groups were recognized, copepoda was a dominant group with 92 species, followed by cladocera (15 species) and tunicata (13 species). Mangrove palm - sea grass had a different zooplankton structure compared with transition area and coral reef with a lower number of species and similarity index about 40%. The average density of zooplankton in study areas in dry season (24,559 ± 24,700 inds.m-3) were 4 times higher than in rainy season (6,124 ± 6.554 inds.m-3) and dominated by copepoda. The euryhaline cladocera (Bosmina longirostris), freshwater cladocera (Ceriodaphnia rigaudi) and freshwater copepoda (Microcyclops varicans) were dominant in mangrove palm - seagrass ecosystem. Meanwhile, in coral reef ecosystem, the small copepods (genus Oncaea, Oithona) and Tunicata were dominant. Biodiversity indices were low in mangrove - palm and increase from transition area to coral reef ecosystem.